Analysis of psychiatric problems in burn patients in a tertiary burn unit: a prospective study - Ramachandran, Manimaran; Durairaj, Alagar Raja; Rao Venkata Mahipathy, Surya Rao; Sundaramurthy, Narayanamurthy (International Surgery Journal, 2017)
Background: Burn injuries in our part of the world generally occurs in the lower socio-economic groups. A large part of these patients suffers from underlying psychiatric disorders. This study is to see the prevalence rates and clinical diagnosis of psychiatric disorders and psychosocial problems as a predisposing factor to burns and squeal to burns in our population, hence necessitate the consultation with the psychiatric team management to improve the outcome from the time of critical phase recovery to the rehabilitation phase. Methods: 114 patients admitted with suicidal burns above the age of 15 years were included in the study at Dept. of Plastic, Reconstructive and Burn Surgery, Govt. Kilpauk Medical College and Hospital for a period of 2 years and evaluated. Results: The patients were mostly married females in the 2nd to 3rd decade of life. Most of them had some form of pre-morbid psychopathology. 60% of patients had >50% burns and only 17% were survivors. After 1 year of psychotherapy, most patients had returned to normalcy. Conclusions: In our study deformity related depression were more after recovery hence prevention of deformity with usage of appropriate splintage, wound management, early grafting and intense physiotherapy will produce a drastic change in their wellbeing and coping ability and help long term rehabilitation and return to normalcy.